A 6-month open-label extension study of the safety and efficacy of subcutaneous belimumab in patients with systemic lupus erythematosus. (August 2018) - Doria, A; Bass, D; Schwarting, A; Hammer, A; Gordon, D; Scheinberg, M; Fox, N L; Groark, J; Stohl, W; Kleoudis, C; Roth, D
Objective: To evaluate the safety, tolerability and efficacy of subcutaneous (SC) belimumab in patients with systemic lupus erythematosus (SLE) beyond 1 year. Methods: This was a 24-week, open-label extension following a 52-week, double-blind, placebo-controlled trial of belimumab SC. Patients who completed the double-blind phase were eligible to enter the open-label phase. All patients received weekly belimumab 200 mg SC plus standard SLE therapy. Outcome measures included safety and efficacy (SLE Response Index (SRI) and SLE Flare Index (SFI) rates), and changes in biomarker and B cell levels. Results: Of 677 patients who completed the 52-week, double-blind phase, 662 entered the open-label phase; 206 had previously received placebo and 456 had previously received belimumab. Despite differences in total belimumab exposure (24 weeks in the placebo-to-belimumab group versus 76 weeks in the belimumab group), the proportions of patients experiencing more than one adverse event (AE) or a serious AE in the open-label phase were similar between groups (placebo-to-belimumab: 51.5 and 6.8%; belimumab: 48.2 and 5.5%, respectively). Most AEs were mild/moderate in severity. Efficacy was maintained through the extension phase. An SRI response was achieved by 16.1% of patients in the placebo-to-belimumab group and 76.3% patients in the belimumab group. Furthermore, 1.0% of patients in the placebo-to-belimumab group and 2.6% of patients in the belimumab group experienced a severe SFI flare. Conclusion: Belimumab SC was well tolerated and efficacy was maintained during the extension phase of this study. The safety profile of belimumab SC is consistent with that of previous experience with belimumab. Trial registration: ClinicalTrials.gov identifier: NCT01484496